2002
DOI: 10.1007/s00412-001-0174-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms regulating the copy numbers of six LTR retrotransposons in the genome of Drosophila melanogaster

Abstract: There has been debate over the mechanisms that control the copy number of transposable elements in the genome of Drosophila melanogaster. Target sites in D. melanogaster populations are occupied at low frequencies, suggesting that there is some form of selection acting against transposable elements. Three main theories have been proposed to explain how selection acts against transposable elements: insertions of a copy of a transposable element are selected against; chromosomal rearrangements caused by ectopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…4. Although different retrotransposon families impose detrimental effects on the host through different mechanisms (Charlesworth and Langley 1989;Carr et al 2002;Petrov et al 2003), the fitness (w) of a chromosome overall can be modeled by a linear function,…”
Section: Forward Simulations Of the Population Genetics Of Pirts And mentioning
confidence: 99%
See 1 more Smart Citation
“…4. Although different retrotransposon families impose detrimental effects on the host through different mechanisms (Charlesworth and Langley 1989;Carr et al 2002;Petrov et al 2003), the fitness (w) of a chromosome overall can be modeled by a linear function,…”
Section: Forward Simulations Of the Population Genetics Of Pirts And mentioning
confidence: 99%
“…The fitness costs of TEs are generally mediated through the following mechanisms: (1) TE insertions disrupt genes (Charlesworth and Charlesworth 1983;Finnegan 1992;McDonald et al 1997); (2) transcription and translation of TE-encoded genes are costly (Brookfield 1991;Nuzhdin 1999); and (3) ectopic recombination among dispersed and heterozygous TEs creates deleterious chromosomal rearrangements (Montgomery et al 1987;Langley et al 1988;Charlesworth and Langley 1989;Petrov et al 2003). It has been demonstrated that different TE families are regulated by different mechanisms, although these mechanisms are not mutually exclusive (Biemont et al 1994;Carr et al 2002;Petrov et al 2003). Despite their being under strong selective pressure, TEs still persist in genomes because they replicate rapidly (Ohta 1983).…”
mentioning
confidence: 99%
“…Their potential to spread through host genomes and populations relies upon their ability to overreplicate the host DNA in the absence of any selective advantage to their carriers, within an evolutionary context that in many respects recalls an ecological community (7). Several mechanisms that may lead to dynamic equilibria of copy number (11), involving either self-regulation of TEs (40) or the opposing forces of transposition and host fitness effects of increased copy numbers (9), have been proposed and tested against observations. These equilibria may persist at some intermediate value for many generations of the host organism, but finally TEs are expected to be eliminated.…”
mentioning
confidence: 99%
“…This suggests that selection against one or more features specific to retroelements leads to their disproportionate elimination from the coding strand of associated genes. While ectopic recombination is likely an important force shaping the distribution of TEs in the genome (Langley et al 1988;Carr et al 2002;Petrov et al 2003), this mechanism cannot plausibly generate the orientation bias of TEs with respect to nearby genes because it operates irrespective of TE orientation. Likewise, it is possible that TEs might insert preferentially in the antisense orientation relative to nearby native genes, but it is not obvious how such a scenario could operate.…”
Section: Te Orientation Bias In Drosophilamentioning
confidence: 99%